Management of Cultivation Business and Utilization on Home Yards for Planting Kale Seeds and Red Shoots Plants - Syamsuri, Abd. Rasyid; Hadian, Arief; Manurung, Hildayani (International Journal Of Community Service, 2022)
Plant cultivation business management is a set of human actions that involves the use of money and other resources to use biological natural resources and process them in order to produce goods that can meet needs. Making good use of the house's yard might have financial advantages. When horticulture crops are grown properly, infertile soil can nevertheless provide productive crops. North Sumatra Province's Suka Damai Village, Kuala District, Langkat Regency, and this Community Service were the locations of this activity. Improved cultivation business management and home yard use for planting green plants and kale seeds are the goals of this community service. 1) Educating participants on the proper techniques for planting kale and red shoots. 2) Help the village population learn the right and proper methods for growing kale and red shoots. 3) May boost individual or community income.